2018
DOI: 10.1155/2018/4813601
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Ferula asafoetida in Functional Dyspepsia: A Randomized, Double‐Blinded, Placebo‐Controlled Study

Abstract: Despite the availability of various synthetic drugs for the treatment of functional dyspepsia (FD), the side effects and their cost have always created a great interest in the search for novel natural alternatives for the management of gut disorders. The present contribution reports the safety and efficacy of the kitchen spice asafoetida (Ferula asafoetida) in FD for the first time. In the double-blinded, placebo-controlled study, 43 subjects diagnosed to have moderate to severe discomforts of nonulcer FD were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…The safety and efficacy of F. assa-foetida on treatment of functional dyspepsia (FD) in a double-blinded, placebo-controlled study showed that treatment with F. assa-foetida (250 mg × 2/day) ( n = 21) for 30 days significantly improved the overall score and quality of life compared to the placebo group. In addition, treatment with F. assa-foetida eliminates and improve the symptoms, including bloating (58%), appetite (69%), postprandial fullness (74%), motion sickness (75%), and indigestion (77%) as compared to less than 10% improvement of symptoms in the placebo group [ 105 ]. The effects of F. assa-foetida mouthwash (10%) twice daily for a period of 7 days compared to chlorhexidine gluconate (CHG) mouthwash (15 ml) were also studied.…”
Section: Resultsmentioning
confidence: 99%
“…The safety and efficacy of F. assa-foetida on treatment of functional dyspepsia (FD) in a double-blinded, placebo-controlled study showed that treatment with F. assa-foetida (250 mg × 2/day) ( n = 21) for 30 days significantly improved the overall score and quality of life compared to the placebo group. In addition, treatment with F. assa-foetida eliminates and improve the symptoms, including bloating (58%), appetite (69%), postprandial fullness (74%), motion sickness (75%), and indigestion (77%) as compared to less than 10% improvement of symptoms in the placebo group [ 105 ]. The effects of F. assa-foetida mouthwash (10%) twice daily for a period of 7 days compared to chlorhexidine gluconate (CHG) mouthwash (15 ml) were also studied.…”
Section: Resultsmentioning
confidence: 99%
“…The association of the asafetida in luence on food transit time [22] and the liver health bene its of milk thistle [23] came out to be a natural prokinetic agent. By improving gastric emptying, gastrointestinal transit time and by regenerating liver intrinsic capacities, the stomach and the liver were treated simultaneously in a way that permit to relieve functional dyspepsia in only 7 days, when other studies with other asafetida formulation without liver active ingredient, obtained signi icant relief in 30 days [24].…”
Section: Discussionmentioning
confidence: 99%
“…With a statistical power of 80% and a one-sided significance level at 5%, this study required a minimum recruitment sample size of 82 patients assuming 15% of the subjects would drop out or fail to follow-up [15].…”
Section: Methodsmentioning
confidence: 99%